2021
DOI: 10.1007/s10803-021-05233-z
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Autistic Children and Their Families During the Pandemic: From Distress to Coping Strategies

Abstract: To understand the perspectives and needs of autistic children and their families in the context of an emergency, 109 parents and 56 autistic children (5.75–18 years) from Canada completed an online survey about needs, barriers and facilitators to coping with the pandemic. Parents’ concerns about their child’s development and difficulties managing their child’s behaviors before and during pandemic were significantly associated. Parents identified maintaining social relationships and implementing appropriate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
0
26
0
2
Order By: Relevance
“…Considering overall activities, one article found a significantly higher engagement in activities prior to the pandemic (Garcia et al, 2021 ), which is in contrast with two papers that observed an increase in overall activity duration (43.3%) (Mete Yesil et al, 2022 ), and more involvement in activities during the pandemic (Mumbardó-Adam et al, 2021 ). Free time also increased for 47.71 to 78.1% of respondents (Colizzi et al, 2020 ; Jacques et al, 2022 ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Considering overall activities, one article found a significantly higher engagement in activities prior to the pandemic (Garcia et al, 2021 ), which is in contrast with two papers that observed an increase in overall activity duration (43.3%) (Mete Yesil et al, 2022 ), and more involvement in activities during the pandemic (Mumbardó-Adam et al, 2021 ). Free time also increased for 47.71 to 78.1% of respondents (Colizzi et al, 2020 ; Jacques et al, 2022 ).…”
Section: Resultsmentioning
confidence: 95%
“…Concerning the period of the COVID-19 pandemic studied, 10 articles (38%) compared before with during the pandemic (Bhat, 2021 ; Cardy et al, 2021 ; Colizzi et al, 2020 ; Garcia et al, 2021 ; Hosokawa et al, 2021 ; Jacques et al, 2022 ; Kawabe et al, 2020 ; Mete Yesil et al, 2022 ; Mutluer et al, 2020 ; Vasa et al, 2021 ), 12 (47%) defined specific pandemic periods (e.g., before versus during quarantine, confinement, or lockdown) (Amorim et al, 2020 ; Berard et al, 2021 ; Bruni et al, 2021 , 2022 ; Levante et al, 2021 ; Lugo-Marín et al, 2021 ; Mumbardó-Adam et al, 2021 ; Tokatly Latzer et al, 2021 ; Türkoğlu et al, 2020 ), while the final four (15%) compared different pandemic moments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper will outline current issues relating to context and policy of Early Intervention in Ireland. It will explore themes in the literature relative to the challenges encountered lacked socialization as a key factor during public health restrictions enforced during the pandemic [10]. Healthcare providers and institutions were challenged in providing services for children with autism and their families.…”
Section: Introductionmentioning
confidence: 99%